Pemberdayaan Guru Muhammadiyah 9 Kota Bengkulu Dalam Penguatan Pendidikan Karakter - Yul, Fadlul Amdhi; Susanto , Edy; Jauhariansyah , Septian; Siska , Jumiati; Sandy , Lengga Satrya (Jurnal Kewirausahaan dan Bisnis, 2021)
Improving the quality of human resources can be done through well-managed education. The success of the educational process is inseparable from the big role of educators. Educators or teachers have a very important role in the success or failure of learning that takes place in schools. This is in accordance with the results of studies from developing countries which prove that teachers make the highest contribution to learning achievement. Information such as the application of computer networks to support competency exam activities. After carrying out the Community Service activity entitled "Empowerment of teachers at SMSK 9 Muhammadiyah Bengkulu City" several results have been achieved, namely: 1. Increased teacher training regarding the goals of teacher empowerment 2. Understanding of forms of teacher empowerment is getting better.